2020
DOI: 10.1016/j.bbalip.2020.158776
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoleic acid reduces high fat diet-induced liver inflammation by promoting PPAR-γ-independent M2a polarization of myeloid cells

Abstract: Palmitoleic acid (POA, 16:1n-7) is a lipokine that has potential nutraceutical use to treat non-alcoholic fatty liver disease. We tested the effects of POA supplementation (daily oral gavage, 300 mg/Kg, 15 days) on murine liver inflammation induced by a high fat diet (HFD, 59% fat, 12 weeks). In HFD-fed mice, POA supplementation reduced serum insulin and improved insulin tolerance compared with oleic acid (OA, 300 mg/Kg). The livers of POA-treated mice exhibited less steatosis and inflammation than those of OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…The present results are in accordance with recent studies that reported decreased IR, hepatic steatosis, and inflammatory reactions in animals receiving HFD after the restoration of the normal PPAR- γ expression by swimming exercises and palmitoleic acid supplementation [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…The present results are in accordance with recent studies that reported decreased IR, hepatic steatosis, and inflammatory reactions in animals receiving HFD after the restoration of the normal PPAR- γ expression by swimming exercises and palmitoleic acid supplementation [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…The role for Plin4 in hepatic steatosis is limited, but it may affect TAG accumulation during HFD feeding ( Griffin, 2017 ). Ablation of Pparg in murine myeloid cells increased insulin resistance ( Souza et al, 2020 ) and ablation in macrophages and hepatic stellate cells, but not hepatocytes increased inflammation ( Morán-Salvador et al, 2013 ). Nevertheless, we did not observe either of these conditions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, their relationships with palmitoleic acid are unclear, since this FA exhibits an anti-inflammatory effect in vitro [50,51], which seems to involve AMPK activation [50]. On the other hand, palmitoleic acid promotes the differentiation of macrophages into the M2 phenotype independent of the lipid sensor PPARγ [52]. In this sense, the balance between FA oxidation and FA synthesis may be essential to macrophage polarization and function.…”
Section: Fatty Acid Overload In Macrophagesmentioning
confidence: 99%
“…This may be why palmitic acid co-stimulates the LPS/TLR-4 system. The anti-inflammatory effects of palmitoleic acid may be due to a reduction in CD36 expression and subsequent decline in FA uptake [52]. Molecular docking experiments showed that palmitoleic acid has a high affinity with the F126 loop site of MD2, a TLR-4 adaptor essential for canonical activation of the TLR-4 pathway.…”
Section: Fatty Acids As Signaling Molecules In Macrophagesmentioning
confidence: 99%